Evidence of a conserved mammalian immunosuppression mechanism in Lutzomyia longipalpis upon infection with Leishmania - Telleria, Erich Loza; Tinoco-Nunes, Bruno; Forrest, David M.; Di-Blasi, Tatiana; Leštinová, Tereza; Chang, Kwang Poo; Volf, Petr; Pitaluga, André Nóbrega; Traub-Csekö, Yara Maria (Frontiers in Immunology, 2023)
Sandflies (Diptera: Phlebotominae) belonging to the Lutzomyia genus transmit Leishmania infantum parasites. To understand the complex interaction between the vector and the parasite, we have been investigating the sand fly immune responses during the Leishmania infection. Our previous studies showed that genes involved in the IMD, Toll, and Jak-STAT immunity pathways are regulated upon Leishmania and bacterial challenges. Nevertheless, the parasite can thrive in the vectors' gut, indicating the existence of mechanisms capable of modulating the vector defenses, as was already seen in mammalian Leishmania infections. In this study, we investigated the expression of Lutzomyia longipalpis genes involved in regulating the Toll pathway under parasitic infection. Leishmania infantum infection upregulated the expression of two L. longipalpis genes coding for the putative repressors cactus and protein tyrosine phosphatase SHP. These findings suggest that the parasite can modulate the vectors' immune response. In mammalian infections, the Leishmania surface glycoprotein GP63 is one of the inducers of host immune depression, and one of the known effectors is SHP. In L. longipalpis we found a similar effect: a genetically modified strain of Leishmania amazonensis over-expressing the metalloprotease GP63 induced a higher expression of the sand fly SHP indicating that the L. longipalpis SHP and parasite GP63 increased expressions are connected. Immuno-stained microscopy of L. longipalpis LL5 embryonic cells cultured with Leishmania strains or parasiteconditioned medium showed cells internalization of parasite GP63. A similar internalization of GP63 was observed in the sand fly gut tissue after feeding on parasites, parasite exosomes, or parasite-conditioned medium, indicating that GP63 can travel through cells in vitro or in vivo. When the sand fly SHP gene was silenced by RNAi and females infected by L. infantum, parasite loads decreased in the early phase of infection as expected, although no significant differences were seen in late infections of the stomodeal valve. Our findings show the possible role of a pathway repressor involved in regulating the L. longipalpis immune response during Leishmania infections inside the insect. In addition, they point out a conserved immunosuppressive effect of GP63 between mammals and sand flies in the early stage of parasite infection.